A new inverse kinematics method for three dimensional redundant manipulators - Mohamed, H.A.F.; Yahya, S.; Moghavvemi, M.; Yang, S.S. (2009)
This paper describes a new geometrical method to solve the inverse kinematic problem for hyper redundant manipulators. The proposed method finds one solution from these infinite solutions. By using this method, the angles between each adjacent links are the same, which makes controlling the movement of these links easier and makes a lining up of two or more joint axes not possible, i.e. very effective for avoiding singularities. A comparison between the proposed manipulator and the PUMA manipulator has been carried out. The manipulability index of both manipulators has been calculated to show the effectiveness of the proposed method. Experiments have been conducted on three links manipulator.